Commercial Activity for Arabian Gulf traders in the Cities of Zanzibar, Mombasa and Lamu on the Eastern Coast of Africa (1939-1890) - Alkassar, Adnan; Almughani, Abdullah (Al-Adab Journal, 2023)
Trade relations between the Arabian Gulf and the East African Gulf and the East African region represented a unique case. Especially because trade between the two regions wasn’t direct and easy. Though it was passing through Arabian Gulf, the Oman sea, the Indian ocean and the Arabian sea to Africa’s east coast cities, most notably Zanzibar, Lamu and Mombasa. Trade was in several sectors; first of which was import and export trade. The second type of trade is the re-export trade that distinguishes the Gulf traders. While the third kind of trade is the commercial repatriation for crops and traded items. Gulf traders have worked to strengthen trade relations between the Arabian Gulf and East Africa by focusing on trade materials exchanged between the two regions. Ignoring the importance of their monopolization of this trade. This led to loss of commercial control over time and it was preceded by the loss of political control. The study concluded the following results: Arabian Gulf traders have worked on the development of commercial routes between the Gulf region and the East Africa for decades. They qualified the area to be a window for commercial activity in the area. Gulf traders have made significant profits in entering the African jungle. In order to reach the main production centers, they maintain the priority of their work in trade without intermediaries. Gulf traders have successfully developed business methods to suit the Gulf’s position halfway between India and East Africa. They worked in the re-export trade achieved significant gains that sustained their presence competitors despite British- Indian control.